The cowboy's Amish haven [large type] - Wright, Pamela Desmond (Love inspired., 2021)
"Her home and her heart are on the line . . . On the same day Gail Schroder's faced with losing her Amish family ranch, her old crush Levi Wyse shows up on hr doorstep. He doesn't know that when he left ten years ago he'd taken Gail's heart with him. Now Levi's her only hope of keeping a roof over her head. But can this cowboy teach Gail the ropes in time to save her home?" --from back cover.